A framework of service-oriented operation model of China׳s power system. (October 2015) - Zhou, Kaile; Yang, Shanlin
Abstract: Based on the rapid development of smart grid and emerging information technologies in China, a new cloud-based power system operational model called Cloud Grid (CG) is presented in this study. CG is a service-oriented operation model of China׳s power system, which integrates the concepts and techniques of cloud computing, big data analytics, internet of things (IoTs), high performance computing, smart grid and other advanced information and communication technologies (ICTs). The power production resources, power production capacities and power resources are virtualized in CG. Moreover, it makes the power system services provided readily available, on-demand, flexible, efficient, safety and reliable for both power producers and electricity consumers. First, the concept and service model of CG are defined, and its system architecture is established. Then, the key techniques of CG are discussed. Finally, we present a brief analysis of the future developments of CG.